O-15 INFECTIONS BY MULTI-DRUG RESISTANT BACTERIA WERE INDEPENDENTLY ASSOCIATED WITH HOSPITAL MORTALITY IN CIRRHOTICS WITH ACUTE DECOMPENSATION: A PROSPECTIVE STUDY ON 433 ADMISSIONS - Gabriela Ruffillo; Juan Cruz Codd; Limbert Jesús Padilla Martínez; Miguel Angel Puga Tejada; Adriana Fernández Lausi; Graciela Landeira; Graciela Priore; Cristina Longo; Gisela Gualano; Nora Domínguez; Maximiliano Socas; Susana di Bartolomeo; et al. (Annals of Hepatology, 2023)
Introduction and Objectives: It has been described as bacterial infections (BIs) due to multidrug-resistant bacteria (MRB) in cirrhosis with acute decompensation (AD), with a potentially poor prognosis. This study aimed to determine the frequency of BIs due to MRB in a tertiary centre and its association with mortality. Materials and Methods: This is a prospective cohort study. Cirrhotics with AD were enrolled. At admission, polymorphonuclear leukocytes (PMN) count was performed in ascites patients. Blood, urine and fluids cultures were collected in patients with encephalopathy, ascites, digestive bleeding or because of IBs suspicion. Sample cultures were repeated during hospitalization when necessary. BIs diagnosis was established based on international consensus. Association among data versus BIs diagnosis was assessed through respective hypothesis testing. Data association with mortality was verified through univariate/multivariate logistic regression: Odds Ratio (OR), 95% confidence interval (CI). Results: A total of 433 inpatients were included: 327 males, median age of 56. Child-Pugh A, B and C were estimated in 22, 197, and 214 cases, respectively, median MELD of 16. BIs were diagnosed in 212/433 (49%) inpatients: 128/212 community-acquired (CA) infections, 22/212 healthcare-associated (HCA) infections and 62 nosocomial infections. The most frequent BIs were spontaneous bacterial peritonitis in 69/212 cases, followed by 59/212 respiratory tract infections and 29/212 urinary tract infections. Bacterial isolation was obtained in 108/212 BIs: 35/108 (32.4%) were MRB. MRB was more frequent in cases with HCA (53%) and nosocomial (41%) infections compared with CA (22%) infections; (P=.0279). Mortality was 17.6% in patients without BIs, 28.8% in non-isolation BIs, 24.7% in non-MRB BIs and 51.4% in BIs due to MRB (P<.001). Multivariate analysis showed that mortality was significantly associated with Child-Pugh C, acute kidney injury, but mainly with MRB BIs (OR 4.41; 95% CI 1.94-10.2; P<.001). Conclusions: MRB frequency was 32.4% among BIs with bacterial isolation. It represents an independent predictor for inpatient mortality.